How is delayed ejaculation defined and treated in North America?. (May 2015) - Butcher, M. J.; Welliver, R.C.; Sadowski, D.; Botchway, A.; Köhler, T. S.
Summary: Delayed ejaculation (DE) is an uncommon disorder that is difficult to treat because it is poorly understood. The aim was to evaluate the current opinion and clinical management of DE by practitioners in sexual medicine. Members of the Sexual Medicine Society of North America (SMSNA) were invited by email to participate in a web‐based survey. The questionnaire consisted of eight questions pertaining to DE. Questions addressed patient volume, qualification of patient bother, ranking of etiologies, perceived success, treatments used, quantification of symptom resolution, and broad characterization of practitioner type. A total of 94 respondents completed the survey with 73% of those being urologists. Fifty‐nine percent of the respondents saw ≤ 2 patients a month with DE and 89% of practitioners felt that DE was moderately or severely bothersome to the patients. Etiology was felt to be from medications and psychological factors primarily. Despite treatment modality, 'seldom' success was obtained for 49% of the time and 'never' for 11%. Carbergoline was the most common selected medication for DE. Academic and private urologists reported 'never' or 'seldom' success with sexual counseling compared to other practitioners, respectively ( p = 0.008 and p = 0.001). Respondents who saw ≤ 2 patients per month often reported normalization of hypogonadism 'never' or 'seldom' corrected DE ( p = 0.047). Delayed ejaculation is still a poorly understood disorder with inconsistent practice patterns seen among members of the SMSNA. A better understanding of this vexing disorder is needed with efforts placed on research and practitioner education.